TRAINING ON THE IMPLEMENTATION OF DEEP LEARNING IN INNOVATIVE LEARNING FOR ELEMENTARY SCHOOL TEACHERS IN TARIK DISTRICT - Ira Eko Retnosari; Erlin Ladyawati; Amelia Widya Hanindita; Bahauddin Azmy (Universitas PGRI Adi Buana Surabaya, 2025)
The purpose of the Community Service activity by the team of lecturers of Elementary School Teacher Education, Faculty of Education, Universitas PGRI Adi Buana Surabaya is to improve teacher competency in knowledge, designing tools, designing deep learning assessments. Teachers who participated in this workshop were able to understand the concept and practice of deep learning better, and were able to implement it in good practice in their respective classes. The results of the analytical discussion that has been described above, it can be concluded that all teachers who participated in the PPM activity by the team of lecturers of the Elementary School Teacher Education Study Program were able to improve their ability to understand the urgency of deep learning, design and use deep learning learning tools. good practice experience of deep learning, development of deep learning learning assessments, and improve the skills of compiling deep learning assessments in elementary schools.